Balancing Offshore Renewable Energy and Marine Conservation in the Blue Economy - Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Jahrizal, Jahrizal; Yovita, Indri; Musa, Sulaiman; Cecilia, Cecilia (Journal of Applied Business and Technology, 2024)
The Blue Economy represents a sustainable approach to harnessing ocean resources for economic growth while preserving marine ecosystems. This study explores the intersection of offshore renewable energy development, particularly wind and tidal energy, and marine conservation. It highlights the significance of adopting innovative technologies, such as floating wind turbines, and emphasizes the role of Marine Spatial Planning (MSP) and Ecological Modernization Theory (EMT) in balancing economic activities with environmental protection. Using qualitative research methods, including semi-structured interviews with stakeholders from renewable energy companies, conservation NGOs, policymakers, and local fishing communities, this study reveals key themes related to policy gaps, innovative solutions, and the necessity of stakeholder collaboration. Findings indicate that existing regulatory frameworks often inadequately address ecological impacts, creating inconsistencies between energy development and conservation efforts. However, advancements in technology and collaborative approaches show promise for minimizing environmental disruption. The research underscores the need for stronger regulatory frameworks that integrate marine conservation into energy development plans. It advocates for community involvement in decision-making processes and the adoption of eco-friendly technologies. By aligning regulatory practices with sustainable development principles, the study presents a pathway toward achieving a balanced Blue Economy, ensuring both economic prosperity and the health of marine ecosystems for future generations. Future research areas are identified to further enhance understanding of the long-term impacts and effective management strategies in this critical field.